Some Issues and Methods of Teaching Foreign Languages to the Students - Tulaganova Dilfuza Abdukabilovna (International Journal on Orange Technologies, 2022)
The concept of a method in language teaching the concept of a systematic set of teaching practices based on a particular theory of language learning has occupied teachers and applied linguists throughout the last century in search of stronger and better methods. Within the methodology, the most common difference between methods and approaches are the technique in which the methods are defined. This article discusses the importance and use of the methods in the process language teaching and learning.